(untitled) (Zaranie Śląskie, 2022)
280 years ago, in 1742, the First Silesian War came to an end. The treaty of Breslau and Berlin resulted in the division of Silesia between Prussia and Austria, both of which happened to fight for this region twice again in the years to come - during the Second Silesian War of 1744-1745 and the Seven-Year War of 1756-1763. However, these two conflicts only confirmed the original division. Throughout the conflict, both sides fought with changing fortunes. The Silesian aristocrats were compelled to choose sides and bear the consequences of their choices, which ranged from being showered with privileges to being imprisoned, from being exiled to being allowed to carry on with their lives and keep their demesne. One of the most important and influential aristocratic families were the Schaffgotsches. Count Johann Anton and his sons experienced all the above mentioned circumstances. The count first fled before the Prussian army, only to return some time later. His son, Prince-Bishop of Breslau, Philipp Gotthard, was first honoured with the highest Prussian military award, the Order of the Black Eagle, but afterwards - exiled from the Prussian part of Silesia. An Austrian rittmeister, Johann Nepomuk, died as a Prussian chamberlain at the royal court in Berlin. Karl Gotthard, having sworn an oath to Prussia, died in the Habsburg ruled Prague. Emmanuel Gotthard died, as a subject of the Prussian emperor, in the last days of the Seven-Year War. The border established in the peace treaty of 1742 is still in existence and today - with some minor differences within the Teschen Silesia - constitutes the state border between the Republic of Poland and the Czech Republic